Vaccination in Patients with Cardiovascular Disease: A Case-Based Approach and Contemporary Review - Sedrak, Phelopater; Dounaevskaia, Vera; Mancini, G.B. John; Zieroth, Shelley; McKelvie, Robert S.; Chiu, Wynne; Bewick, David; Ducharme, Anique; Mansour, Samer; Lepage, Serge; Pearson, Glen J.; Welsh, Robert C.; et al. (CJC open (Online), 2025)
Vaccination is a crucial preventative strategy, particularly in individuals with cardiovascular (CV) disease (CVD). People living with CVD are at increased risk of morbidity and mortality from vaccine-preventable infections such as influenza, severe acute respiratory syndrome-corona virus 2 (SARS-CoV-2), respiratory syncytial virus (RSV), varicella zoster virus (VZV), and pneumococcal disease. These infections also have been associated with downstream CV complications, including ischemic events and myocarditis. Randomized controlled trials have demonstrated that influenza vaccination reduces major adverse CV events and all-cause mortality, especially in people with CVD. The same has been observed in registry analyses during the SARS-CoV-2 pandemic. Pooling of data from observational and cohort studies also has shown significant benefit of vaccination against RSV, VZV, and pneumococcal disease in older populations and those with CV comorbidities. Despite recommendations from national public health guidelines and immunization programs, vaccination uptake in patients with CVD remains suboptimal. This low uptake is influenced by lack of vaccine information, access issues, and mistrust in the healthcare system, all summarized in the term “vaccine hesitancy.” Vaccination promotion should focus on addressing these gaps in communication and access barriers at the provider, community, and public health levels. Healthcare providers including cardiologists are reminded, through this review, of the importance of emphasizing vaccination recommendations during clinical encounters. Addressing patient misconceptions and providing patient decision aids strongly improves acceptance rates. Continued efforts at the community and public health levels should address barriers to access and advance surveillance methods to target improved clinical outcomes for groups at risk. La vaccination constitue une stratégie préventive cruciale, en particulier chez les personnes atteintes de maladie cardiovasculaire (MCV). Les personnes souffrant de MCV courent un risque accru de morbidité et de mortalité liées à des infections évitables par la vaccination, telles que la grippe, le SRAS-CoV-2, le virus respiratoire syncytial (VRS), le virus varicelle-zona (VZV) et les infections à pneumocoque. Ces infections ont également été associées à des complications cardiovasculaires secondaires, notamment des événements ischémiques et des myocardites. Des essais contrôlés randomisés (ECR) ont démontré que la vaccination contre la grippe réduit les événements cardiovasculaires indésirables majeurs et la mortalité toutes causes confondues, en particulier chez les personnes atteintes de MCV. Le même phénomène a été observé dans les analyses des registres pendant la pandémie de SRAS-CoV-2. La mise en commun des données issues d'études observationnelles et de cohortes a également montré les avantages significatifs de la vaccination contre le VRS, le VZV et les infections à pneumocoque chez les personnes âgées et celles présentant des comorbidités cardiovasculaires. Malgré les recommandations des lignes directrices nationales de santé publique et des programmes de vaccination, la couverture vaccinale chez les patients atteints de MCV reste insuffisante. Cela s'explique par le manque d'informations sur les vaccins, les problèmes d'accès et la méfiance à l'égard du système de santé, tous ces facteurs étant résumés par le terme « hésitation vaccinale ». La promotion de la vaccination devrait se concentrer sur la résolution de ces problèmes de communication et d'accès au niveau des prestataires de soin, des communautés et de la santé publique. Cette étude rappelle aux prestataires de soins de santé, y compris aux cardiologues, l'importance de mettre l'accent sur les recommandations en matière de vaccination lors des consultations cliniques. Le fait de dissiper les idées reçues des patients et de leur fournir des aides à la décision améliore considérablement les taux d'acceptation. Des efforts continus au niveau communautaire et de la santé publique devraient viser à éliminer les barrières d'accès et à perfectionner les méthodes de surveillance afin d'améliorer les résultats cliniques pour les groupes à risque.